The Emergence of Jadid Enlightenment on the Path of National Liberty - Qurbanovich, Amirxo’jayev Shukurjon (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
issues such as the emergence of Jadid enlightenment and the formation of statehood ideas, the importance of Jadid press in socio-political processes, the implementation of national and statehood ideas of the Jadids, the role of the Jadid intelligentsia in the development of Uzbek culture, the importance of new method schools in the promotion of the national ideas of the Jadids are highlighted.